Developing and promoting community participation in the control of dengue haemorrhagic fever vectors - Sugeng Juwono Mardihusodo, Sugeng Juwono Mardihusodo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1987)
Dengue haemorrhagic fever (DHF) is caused by dengue virus and transmitted by Aedes aegypei and A e. albopictus mosquitoes. The absence of causative drugs and protective vaccines, therefore, indicates vector control measures as the only alternative for the disease abatement. Various methods of dengue vector control and of developing and promoting community participation in such activities are discussed. Key Words: dengue haemorrhagic fever Ã¢â¬â Aedes aegypti Ã¢â¬â Breteau Index Ã¢â¬â environmental sanitation Ã¢â¬â Rural Improvement Programme